PENERAPAN ALAT PENGASAPAN IKAN RAMAH LINGKUNGAN DI KAMPUNG NELAYAN BANGKO BANGKO SEKOTONG LOMBOK BARAT - Sujita Darmo; Zainuri Achmad; I Made Adi Sayoga; Nur Kaliwantoro; Ida Bagus Alit (Jurnal Abdi Insani, 2022)
Bangko Bangko is a fishing village located in Bangko Bangko Bay, Batuputih Village, Sekotong District, West Lombok, West Nusa Tenggara. In the fishing village of Bangko-Bangko, only 60 families live, with a livelihood as fishermen and fishing. Because the position of the bay has sufficient waters, so many fish can be caught, especially tongkol. Around 200 fishing boats docked in Bangko Bangko Bay, with the catch in the form of tuna. The abundance of tuna catches resulted in a low price, 5 thousand per kg of fresh fish and 7.5 thousand for pindang fish per bamboo package containing 5 fish. The purpose of the service activities that have been carried out in August 2018 is to increase the selling price of tuna. The method of activity to increase the selling price of tongkol by processing it into smoked fish, using an environmentally friendly fish smoking device. As a result, the smoked fish produced has a more savory aroma, a distinctive smoke smell, so the price increases for packaging ranging from 12.5 to 15 thousand rupiah. Smoked fish is relatively more durable than fresh fish and pindang fish, so the distribution of sales reaches Mataram City. Other activity outputs are in the form of transfer of skills in manufacturing techniques and steps for implementing environmentally friendly fish smoking, as well as manuals on smoking fish techniques. The application of environmentally friendly fish smoking tools in this community service program can improve the welfare of the fishing village of Bangko Bangko and its surroundings.